2017
DOI: 10.7860/jcdr/2017/24290.9976
|View full text |Cite
|
Sign up to set email alerts
|

Study of Vitamin D Receptor Gene Polymorphism (FokI, TaqI and ApaI) Among Prostate Cancer Patients in North India

Abstract: Introduction: Incidence of prostate cancer is rising worldwide. Multiple factors have been suggested for the aetiology of prostate cancer including ethnic, genetic and diet. Vitamin D (calcitriol) has been shown to have role in cell growth and differentiation and its deficiency is implicated as one of the aetiological factors in prostate cancer. Prostatic epithelial cells express Vitamin D Receptor (VDR) as well as 1α-hydroxylase enzyme that are required for the synthesis of calcitriol and its action. Polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The number of cases and controls varied from 28 to 1,617, and 41 to 1,072, respectively (Table 1 ). The genotype distribution frequency in the control groups was consistent with Hardy-Weinberg equilibrium (HWE) for most studies, except for four studies [ 12 , 19 , 25 , 49 ]. Each individual study scored more than 4 by Newcastle-Ottawa Scale (NOS), and was considered to be of high quality (Table 1 ).…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…The number of cases and controls varied from 28 to 1,617, and 41 to 1,072, respectively (Table 1 ). The genotype distribution frequency in the control groups was consistent with Hardy-Weinberg equilibrium (HWE) for most studies, except for four studies [ 12 , 19 , 25 , 49 ]. Each individual study scored more than 4 by Newcastle-Ottawa Scale (NOS), and was considered to be of high quality (Table 1 ).…”
Section: Resultssupporting
confidence: 54%
“…Previous meta-analyses were reported by Yin et al in 2009, Fei et al in 2016 and Liu et al in 2017 [ 10 , 23 , 24 ], in which the number of included studies was 23, 27 and 8, respectively. However, some new data was reported, which is not consistent with the results of the former three studies [ 17 , 25 27 ]. 8,423 cases and 8,867 controls were included in our analysis from 36 independent studies.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…It was shown that vitamin D (calcitriol) influences on prostate cancer cells growth [16]. Furthermore, the TMPRSS2-ERG fusion expression is increased upon activation of VDR and AR.…”
mentioning
confidence: 99%